Effects of two-year nutrient loading on microbial community and N transformations in mineral and organic soils of wet meadows - Mach, Jiří (Jihočeská univerzita, 2010)
This study observes an influence of two-year application of NPK fertilizer on the amount of soluble nitrogen, microbial N transformations, and microbial biomass and the composition of microbial community in mineral and organic soils of two wet meadows. This study is the first version of manuscript, supplemented with a wider literature review, which will be submitted in 2010.
Effects of two-year nutrient loading on microbial community and N transformations in mineral and organic soils of wet meadows
Keywords: wet meadows; fertilization; eutrophication; microbial community; soil nitrogen cycle; nitrogen transformations